Anisotropic molecular hopping at the solid–nematic interface1. Issue 39 (21st October 2015) - Chakraborty, Saonti; Nelson, Nathaniel; Schwartz, Daniel K.
<x xml:space="preserve">Abstract</x> Single molecule tracking was used to observe intermittent and anisotropic molecular motion at the solid–nematic interface.